Why parties ?: A second look - Aldrich, John H. (Chicago The University of Chicago Press, 2011)
Since its first appearance fifteen years ago, Why Parties? has become essential reading for anyone wishing to understand the nature of American political parties. In the interim, the party system has undergone some radical changes. In this landmark book, now rewritten for the new millennium, John H. Aldrich goes beyond the clamor of arguments over whether American political parties are in resurgence or decline and undertakes a wholesale reexamination of the foundations of the American party system.